Relationship between thirty minute maximal rowing ergometer performance and blood lactate measures - Smith, T. B.; Sleivert, G. (Medicine & Science in Sports & Exercise, 1999)
This study determined if the pace of an ergometer task performed at close to a competitive oarsman's anaerobic threshold could be predicted by different threshold measures determined from an incremental blood lactate test. Elite oarsmen (N = 8) completed a 30-minute maximal test followed one week later by an incremental blood lactate test to maximum. Average power output from the 30-minute test was compared to the power outputs determined from five different blood lactate threshold measures (deflection point, 4 mM/l, maximal perpendicular distance from both end points of the lactate curve, and lactate threshold). Threshold measures, except the lactate threshold, correlated significantly with the 30-minute task time. However, paired-T tests were significantly different. This meant that while the measures were associated, the amount of residual difference was significant. Implication. No threshold measures accurately predict the workload for a maximal 30-minute rowing ergometer test in competitive oarsmen. Threshold measures are not good work predictors for rowing.